2020
DOI: 10.1101/2020.12.11.421180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal scaling of human scalp-recorded potentials

Abstract: Standard event-related potential analysis assumes fixed-latency responses relative to experimental events – yet recent single unit recordings have revealed neural activity scales to span different durations during behaviours demanding flexible timing. We use a novel approach to unmix fixed-time and scaled-time components in human electroencephalography, recorded across three tasks. A consistent and distinct scaled-time component is revealed, demonstrating temporal scaling can reliably be measured at the scalp.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
(168 reference statements)
0
10
0
Order By: Relevance
“…Finally, and perhaps most importantly, the experimenter-controlled sensory noise allows us to characterise how continuous sensory evidence fluctuations cause changes in the simultaneously recorded continuous EEG signal. To study this, we used a deconvolutional general linear model (GLM) approach (Crosse et al, 2016; Ehinger and Dimigen, 2019; Gonçalves et al, 2014; Hassall et al, 2021) to estimate temporal response functions (TRFs) to various events relating to the time-varying sensory evidence. We describe this approach and the resulting TRFs in more detail below.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, and perhaps most importantly, the experimenter-controlled sensory noise allows us to characterise how continuous sensory evidence fluctuations cause changes in the simultaneously recorded continuous EEG signal. To study this, we used a deconvolutional general linear model (GLM) approach (Crosse et al, 2016; Ehinger and Dimigen, 2019; Gonçalves et al, 2014; Hassall et al, 2021) to estimate temporal response functions (TRFs) to various events relating to the time-varying sensory evidence. We describe this approach and the resulting TRFs in more detail below.…”
Section: Resultsmentioning
confidence: 99%
“…Another phenomenon to consider is that of temporal scaling. Prior work has shown that rather than occurring at fixed latencies relative to events, certain neural responses can stretch or compress to fill a stimulus-response gap [96][97][98]. When characterizing particular neural responses, it is important to understand whether the response occurs at a fixed latency, or if it scales with the stimulusresponse gap.…”
Section: The Importance Of a Post-stimulus Gapmentioning
confidence: 99%
“…Another phenomenon to consider is that of temporal scaling. Prior work has shown that rather than occurring at fixed latencies relative to events, certain neural responses can stretch or compress to fill a stimulus-response gap [95][96][97]. When characterizing particular neural responses, it is important to understand whether the response occurs at a fixed latency, or if it scales with the stimulus-response gap.…”
Section: The Importance Of a Post-stimulus Gapmentioning
confidence: 99%